Assistance in developing anti-corruption gymnastic creations–dare, to be responsible, independent, and honest (BeTa MaJu)- based on creative imagination in Islamic religious learning - Desfa Yusmaliana; Oktarina Oktarina; Gamal Abdul Nasir Zakaria; Aji Kurbiyanto; Jesika Jesika; Antika Purnama Sari (Community Empowerment, 2023)
PAUD/TK, SD and SMP Desa Batu Beriga are educational institutions that that take the lesson on the importance of applying integrity values such as courage, responsibility, independence and honesty. For this reason, the educational institution incorporates the values of integrity into learning. The Corruption Eradication Commission (KPK) carries out corruption prevention through anti-corruption exercises which can be accessed and implemented in schools. Groups of KB/TK, SD, and SMP teachers should also be able to develop creativity in these activities which can be used as learning materials at school. This service aims to provide training on making creations of Anti-Corruption-Dare to Be Honest Independent Responsibility (BeTa Maju) creations based on creative imagination in Islamic religious learning for Early Childhood for PAUD/Kindergarten, Elementary and Middle School Teachers in Batu Beriga Village, Central Bangka Regency. This service uses the participatory action research (PAR) method where the service team collaborates with partners to find solutions together supported by socialization by the service team according to the area of expertise. In the end, through training activities for making anti-corruption gymnastic creations, teachers in Batu Beriga village can create their own anti-corruption gymnastics at their respective schools and have the potential to become one of the programs in the anti-corruption education model at school.